Does Explicit Polarizability Improve Simulations of Phase Behavior of Ionic Liquids? - Klajmon, Martin; Červinka, Ctirad (Journal of chemical theory and computation, 2021)
Molecular dynamics simulations are performed for a test set of 20 aprotic ionic liquids to investigate whether including an explicit polarizability model in the force field leads to higher accuracy and reliability of the calculated phase behavior properties, especially the enthalpy of fusion. A classical nonpolarizable all-atom optimized potentials for liquid simulations (OPLS) force-field model developed by Canongia Lopes and Pádua (CL&P) serves as a reference level of theory. Polarizability is included either in the form of Drude oscillators, resulting in the CL&P-D models, or in the framework of the atomic multipole optimized energetics for biomolecular application (AMOEBA) force field with polarizable atomic sites. Benchmarking of the calculated fusion enthalpy values against the experimental data reveals that overall the nonpolarizable CL&P model and polarizable CL&P-D models perform similarly with average deviations of about 30%. However, fusion enthalpies from the CL&P-D models exhibit a stronger correlation with their experimental counterparts. The least successful predictions are interestingly obtained from AMOEBA (deviation ca. 60%), which may indicate that a reparametrization of this force-field model is needed to achieve improved predictions of the fusion enthalpy. In general, all FF models tend to underestimate the fusion enthalpies. In addition, quantum chemical calculations are used to compute the electronic cohesive energies of the crystalline phases of the ionic liquids and of the interaction energies within the ion pair. Significant positive correlations are found between the fusion enthalpy and the cohesive energies. The character of the present anions predetermines the magnitude of individual mechanistic components of the interaction energy and related enthalpic and cohesive properties.